Strawberry cultivars fruit production and postharvest from two types of saplings - Chiomento, José Luís Trevizan; dos Santos Trentin, Thomas; Fernandes de Lima Turmina, Ana Paula; Fornari, Michele; Viau Dos Santos, Matheus; Trevisan de Miranda, Débora (Scientia Agraria Paranaensis, 2021)
The establishment of strawberry crops in southern Brazil is conditioned on the delivery of bare-root saplings imported from Argentina and/or Chile. An alternative to reduce dependence on the acquisition of these saplings is their replacement by clod-rooted saplings that form a clod. However, information on the agronomic performance of clod-rooted saplings is scarce. The aim of this work was to investigate whether the association between types of saplings and strawberry cultivars alters fruit production and postharvest. The research was carried out at the Horticulture Sector of the University of Passo Fundo, Passo Fundo, Rio Grande do Sul, Brazil, from March to December 2020, in a greenhouse. The plant material for the research consisted of saplings with bare-roots and saplings rooted in clods. The treatments were three cultivars (‘Fronteras’, ‘Monterey’ and ‘Portola’) and two types of saplings (bare-root and rooted in a clod), arranged in a randomized block design, with three replications and ten plants per plot. The productive potential and chemical quality of fruits were evaluated. Plants from saplings rooted in clods showed higher number and fruit production. Plants from bare -root saplings produced larger fruits. The postharvest of fruits was not altered by the treatments. The productive potential and postharvest of fruits of strawberry cultivars are not associated with the different types of saplings studied. Regardless of the cultivar used, plants from saplings rooted in clods have greater productive potential compared to plants from bare-root saplings. The fruits of the three cultivars tested in this study, from saplings with bare-roots or rooted in clods, present a balanced relationship between sugar and acidity, which makes the strawberries suitable for consumption.